117k views
3 votes
How do you do this question?

How do you do this question?-example-1
User Snacky
by
5.8k points

1 Answer

6 votes

Answer:

Cartesian Equation: y = √(1 - x^2)

Graph: Second one

Explanation:

x^2 = sin^2(θ/2),

y^2 = cos^2(θ/2),

According to that theory, by the circle equation, x^2 + y^2 = 1^2.

When θ = -π, x = sin(-π/2) = - 1, and y = cos(-π/2) = 0

When θ = π, x = sin(π/2) = 1, and y = cos(π/2) = 0

The radius is 1 in this case, (x^2 + y^2 = r^2 -> x^2 + y^2 = 1^2 -> x^2 + y^2 = 1) as the semicircle ranges from (- 1, 0) to (1,0). Therefore your graph is the second one;

When theta = 0, x = sin 0 = 0, and y = cos 0 = 1, so the semicircle passes through (0, 1). To determine the equation, let's simply isolate "y" in the equation x^2 + y^2 = 1^2,

In Cartesian form, the equation is y = √(1 - x^2)

How do you do this question?-example-1
User Aatif Farooq
by
5.0k points